The influence factors toward personal improvement and employment outcomes - Lee, Cheng Wen; Kusumah, Alum (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2018)
This study has the background of companies that place their workers only as input factors (assets) but do not place them as equal partners who need each other, related in be up against increasingly complex challenges and to develop the organization. Values and norms poorly governed and rarely well developed; therefore, organizations merely assign workers as the assets rather than as power resource. The research objective is to examine the factors that influence personal improvement and employment outcomes at PAA Company. The population utilized is all PAA company with a total of 273 employees with 152 respondents taken as samples. Data collection through the distribution of questionnaires which then processed and analyzed using multiple linear regression data analysis techniques with SPSS 20.00 for Windows. The result of the variables tested represents as follows: the meaning of work, responsibility, and awareness of work activities' outcome simultaneously has a significant effect on personal improvement and employment outcomes. The variable of the meaning of work & responsibility by partially does not have a significant influence. On the direct contrary, awareness of work activities' outcome partially has a significant influence on personal improvement and employment outcomes.